2012
DOI: 10.4251/wjgo.v4.i11.223
|View full text |Cite
|
Sign up to set email alerts
|

Omission of breakfast and risk of gastric cancer in Mexico

Abstract: Our study suggests an association between the omission of breakfast and the failure to refrigerate food with GC in the Mexican population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, some studies found no connection between breakfast skipping and weight status, while others have claimed that breakfast skipping can help lose body weight (18,19). Breakfast skipping has also been related to a higher risk of various non-communicable diseases, such as cardiovascular disease, type 2 diabetes, and certain malignancies (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies found no connection between breakfast skipping and weight status, while others have claimed that breakfast skipping can help lose body weight (18,19). Breakfast skipping has also been related to a higher risk of various non-communicable diseases, such as cardiovascular disease, type 2 diabetes, and certain malignancies (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori virulence is determined by genes such as the pathogenicity island cagPAI, the vacuolating cytotoxin VacA, and adhesion proteins including BabA or SabA . Also, a diet rich in salt and poor in antioxidants, as well as smoking, and alcohol consumption favors the development of GC . Regarding host factors, polymorphisms in genes related to inflammation and innate immunity, such as cytokines and HLA, have been reported to be associated with an increased risk for GC.…”
mentioning
confidence: 99%
“…5,7 Also, a diet rich in salt and poor in antioxidants, as well as smoking, and alcohol consumption favors the development of GC. 2,8 Regarding host factors, polymorphisms in genes related to inflammation and innate immunity, such as cytokines and HLA, have been reported to be associated with an increased risk for GC. Among the cytokines that have been associated with GC are polymorphisms in IL-1B (-511T and -31C), IL-1RN*2/*2, IL-4 -590T, IL-6 (-590T and -174G), TNF-a -308A, TNF-b +252A, and HSP70-1 +190C, [9][10][11][12][13] although results vary across populations.…”
mentioning
confidence: 99%
“…A Mexican study found association of skipping breakfast with gastric cancer [99] which is third most common cancer in men and the fifth in women. Frequent deviation in meal timing over a prolonged period appears associated with increased risk of developing HP infection and gastritis [100].…”
Section: Abdominal Discomfort Ulceration and Cancermentioning
confidence: 99%